Clinical Transplantation of Individualized Recipient Serum-Adapted Cornea Reduces the Risk of Graft Rejection after Keratoplasty. Issue 3 (March 2013) - Thanos, Solon; Gatzioufas, Zissis; Schallenberg, Maurice; König, Simone; Meyer-Rüsenberg, Hans-Werner; Busse, Holger
Corneal diseases cause severe visual impairment that necessitates corneal transplantation and frequently repetitive procedures due to graft rejection. We tested the hypothesis that exposure of donor corneas to recipient serum-derived factors during eye banking triggers a preoperative adaptation that is beneficial for postoperative tolerance. Donor corneas were incubated in a medium containing human serum (HS) obtained in each case from the prospective graft recipient in order to individually expose the donor cornea to the recipient's serum. All recipient serum-adapted corneas (RSACs) fulfilled the clinical criteria required by the national law and were transplanted successfully. The postoperative ophthalmological examination extended up to 8 years. All RSACs were tolerated by their recipients and did not cause postoperative complications and no rejection. Proteomic analysis of corneas cultivated in culture medium containing either fetal calf serum (FCS) that is routinely used for cornea banking or HS revealed different patterns of proteins. HS-cultured corneas showed a greater proteomic similarity with native human corneas than did the FCS-cultured corneas, indicating a differential nutrification of the cultured corneal tissue by HS-derived factors. The clinical results show for the first time that postoperative complications such as tissue intolerance and graft rejection might be managed if the corneal tissue is individually adapted to the recipient's serum trophic factors. This new donor tissue treatment procedure offers incontrovertible advantages and could be adapted for low-risk eyes as well as other transplantable tissues.